2017
DOI: 10.1038/s41598-017-08451-7
|View full text |Cite
|
Sign up to set email alerts
|

Culture independent assessment of human milk microbial community in lactational mastitis

Abstract: Breastfeeding undoubtedly provides important benefits to the mother-infant dyad and should be encouraged. Mastitis, one of the common but major cause of premature weaning among lactating women, is an inflammation of connective tissue within the mammary gland. This study reports the influence of mastitis on human milk microbiota by utilizing 16 S rRNA gene sequencing approach. We sampled and sequenced microbiome from 50 human milk samples, including 16 subacute mastitis (SAM), 16 acute mastitis (AM) and 18 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
134
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 52 publications
16
134
3
9
Order By: Relevance
“…For instance, bacterial dysbiosis has been described in lactating mothers suffering from breast pain and/or mastitis (Jimenez et al, 2008;Jiménez et al, 2015;Maldonado-Lobón et al, 2015;Mediano et al, 2017). In mastitis cases, the milk microbiota reflects a loss of bacterial diversity and a high increase in the abundance of the sequences related to the presumptive etiological agents such as Staphylococcus aureus and Staphylococcus epidermidis in acute and subacute mastitis, respectively (Jiménez et al, 2015;Patel et al, 2017). Likewise, in bovine, both clinical and subclinical intramammary infections are associated with changes in milk microbiota (Oikonomou et al, 2012(Oikonomou et al, , 2014Kuehn et al, 2013;Falentin et al, 2016;Lima et al, 2017).…”
Section: Milk Microbiota: Role For Mother and Infant Health Milk Micrmentioning
confidence: 99%
“…For instance, bacterial dysbiosis has been described in lactating mothers suffering from breast pain and/or mastitis (Jimenez et al, 2008;Jiménez et al, 2015;Maldonado-Lobón et al, 2015;Mediano et al, 2017). In mastitis cases, the milk microbiota reflects a loss of bacterial diversity and a high increase in the abundance of the sequences related to the presumptive etiological agents such as Staphylococcus aureus and Staphylococcus epidermidis in acute and subacute mastitis, respectively (Jiménez et al, 2015;Patel et al, 2017). Likewise, in bovine, both clinical and subclinical intramammary infections are associated with changes in milk microbiota (Oikonomou et al, 2012(Oikonomou et al, , 2014Kuehn et al, 2013;Falentin et al, 2016;Lima et al, 2017).…”
Section: Milk Microbiota: Role For Mother and Infant Health Milk Micrmentioning
confidence: 99%
“…Functional metagenomics identified several gene pathways in bacterial secretion system and motility proteins related to bacterial proliferation and colonization in sub-acute and acute mastitis samples. It was reported that ∼45% of genes belonged to metabolism, 18% to environmental information and processing, 14% to genetic information processing, and 1% to human diseases (57).…”
Section: Milk Microbiomementioning
confidence: 99%
“…First of all, the bacteria on the skin surface can intrude through the cracked nipple and areola, and retrograde to interlobular mammary gland. Second, the microorganisms in the baby's mouth enter the mammary duct and stay in it [39]. Finally, some studies suggest [16,40] that there is an endogenous pathway existing in the source of microbes of milk, which involve in bacterial infections in other parts of the postpartum (such as respiratory infections, acute tonsillitis etc.)…”
Section: Discussionmentioning
confidence: 99%